Inovação tecnológica e o mercado de trabalho do engenheiro cartógrafo - Da Silva, João Fernando Custódio [UNESP] (My University, 2006)
The article focuses on the presence of the technologic innovation and the surveyed current conditions of the cartographic engineer's work market. The methodology is based on forms with objective questions answered by the professionals. The current survey is the fourth one starting in 1995 and the first one with on line forms filled out by the Brazilian Association of Cartographic Engineers - São Paulo Section's web page. The sample was made up with 141 engineers and it revealed numbers that confirm the growing visibility and social recognition of the Brazilian cartographic engineer, although still far from the condition consistent with the territorial extension and the importance of Cartography for the country. The survey shows that the monthly average revenues are of approximately fifteen minimum wages; that the sample has only 13% of employers, although it is the highest percentage among all surveys; that 63 professionals cited 127 times that their organizations are related to technologic innovation at a proportion of two citations per organization; that 69% of the sample are optimists concerned to the future. Other important pieces of in formation to students and professionals will also be discussed in the article.
Technologic innovation and the cartographic engineer's work market
Keywords: Cartographic engineering; Technologic innovation; Work market; cartography; innovation; technological change